Sister Mary Joseph’s Nodule as the Sole Presenting Feature of Disseminated Squamous Cell Cancer of the Esophagus: A Rare Case - Wijekoon, N. S.; Samarasekera, D. N. (Springer-Verlag, 2008)
Umbilical nodule due to tumor metastasis is a rare presentation which is known as Sister Joseph’s nodule. This is usually due to disseminated intra abdominal malignancies which are mostly adenocarcinomas. Esophageal squamous cell cancer commonly presents with progressive dysphagia, and it usually metastasizes to liver, lungs, bones, and regional lymph nodes; however, spreading to the umbilicus is an extremely rare occurrence. In this paper, we report a 77-year-old man presenting with a painful umbilical nodule as the only presenting feature of disseminated, poorly differentiated squamous cell carcinoma of the esophagus.
Keywords: Sister Joseph’s nodule; esophageal cancer